The Effect of Viral Marketing and E-Service Quality on Consumer Buying Interest in Disney+ Hotstar Services - Raihan Syihab, Rama; Ridanasti, Erlita (CV. Publikasi Indonesia, 2024)
This research was conducted with the aim of determining the influence of Viral Marketing and E-Service Quality on Consumer Purchase Interest in the Disney+ Hotstar Indonesia service. The population in this study is residents who are users or residents who know the Disney+ Hotstar Indonesia Video on Demand service in the Yogyakarta area. This research uses a quantitative approach, with data collection techniques using questionnaires distributed online. The sampling technique used purposive sampling with a sample of 180 respondents. The data analysis used in this research is multiple linear regression analysis with the Moderated Regression Analysis (MRA) test which is processed with IBM SPSS Statistics 26.0 software. The results of this research show that Viral Marketing has a positive and significant influence on Consumer Purchase Interest. Meanwhile, E-service Quality has a positive and significant influence on Business Model Innovation. It was also found that organizational risk-taking tolerance is a factor in consumer buying interest. And the Viral Marketing and E-Service Quality variables together have a positive and significant effect on Consumer Purchase Interest.